1998
DOI: 10.1152/ajpregu.1998.275.6.r1725
|View full text |Cite
|
Sign up to set email alerts
|

β-Endorphin and natural killer cell cytolytic activity during prolonged exercise. Is there a connection?

Abstract: This study was designed to test whether a single 50-mg dose of the opioid antagonist naltrexone hydrochloride, ingested 60 min before 2 h of moderate-intensity exercise (i.e., 65% peak O2 consumption), influenced the exercise-induced augmentation of peripheral blood natural killer cell cytolytic activity (NKCA). Ten healthy male subjects were tested on four occasions separated by intervals of at least 14 days. A rested-state control trial was followed by three double-blind exercise trials [placebo (P), naltrex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Various authors observed stimulatory and inhibitory effects mainly on mixed cell fraction [4]. For example, the production of γ-IFN was suppressed by a mechanism realized through µ-receptor on monocytes and stimulated through a nonopioid receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Various authors observed stimulatory and inhibitory effects mainly on mixed cell fraction [4]. For example, the production of γ-IFN was suppressed by a mechanism realized through µ-receptor on monocytes and stimulated through a nonopioid receptor.…”
Section: Resultsmentioning
confidence: 99%
“…A double blind randomised block trial used oral naloxone to counter -endorphin, 61 and indomethacin to counter prostaglandin release. 62 The -endorphin antagonist had no eVect other than to reduce the exercise induced increment of -endorphin, but prostaglandin levels did increase during vigorous aerobic activity.…”
Section: Effect Of Anti-inflammatory Agents and Endorphin Antagonistsmentioning
confidence: 99%
“…1999). Surface density of CD2 on CD56+ NK cells has also been shown to decrease after prolonged, low intensity exercise (Gannon et al . 1998).…”
mentioning
confidence: 99%